MENATA ULANG PARADIGMA PENDIDIKAN MASA DEPAN DALAM MENGHADAPI TANTANGAN GLOBAL - Aini, Nur; Handoko, Yudo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the need to reconstruct the paradigm of future education in response to increasingly complex global challenges, including technological disruption, cultural shifts, and the demands of 21st-century competencies. The problem addressed in this research is the mismatch between conventional educational approaches and the dynamic needs of global society. The objective of this study is to analyze and formulate a more adaptive, innovative, and holistic educational paradigm. This research employs a qualitative approach using a literature study method, where data are collected from various relevant books, journals, and scientific publications from the last five years. The analysis is conducted through data reduction, data display, and conclusion drawing to identify key patterns and concepts. The findings reveal that future education must emphasize flexibility in curriculum design, integration of technology, development of critical thinking skills, and strengthening of character education based on global and local values. In addition, collaboration between stakeholders and continuous innovation in learning strategies are essential to ensure the relevance and sustainability of education systems. Therefore, restructuring the educational paradigm is crucial to prepare learners who are competent, adaptive, and competitive in the global era